AI & ML algorithms and their practical applications - Barton, Robert; Henry, Jerome (Pearson, 2024)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing.
Online resource; title from title details screen (O'Reilly, viewed September 9, 2024)
Keywords: Artificial intelligence; Machine learning; Algorithms; Intelligence artificielle; Apprentissage automatique; Algorithmes; artificial intelligence; algorithms; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet